Effect of Heat Shock Treatment and Aloe Vera Coating on Chilling Injury Symptom in Tomato (Lycoperiscon asculantum Mill) - Sutrisno .; Yohanes Aris Purwanto; Ismi M.Idris; Olly S. Hutabarat; Sugiyono . (PERTETA, 2010)
AbstractThis research was undertaken to determine the effect of length in heat shock and edible coating as prestorage treatment on Chilling Injury (CI) symptom reflected by ion leakage induced and quality properties in tomato (Lycopersicon asculantum Mill.). Heat Shock Treatment (HST) was conducted at three different levels of length, which were, 20, 40 and 60 min. Edible coating was conducted using aloe vera gel. The result showed that HST and Aloe Vera Coating (AVC) were more effective to reduce CI symptom at lower chilling storage. Prolong exposure to heated water may delay climacteric peak. The length of heat shock; AVC treatment and low temperature storage significantly affected the tomato quality parameter but not significantly different for each treatment except weight loss. HST for 20 min at ambient temperature was significantly different to other treatment.Keywords: ion leakage, chilling injury, climacteric, shelf-lifeDiterima: 2 Desember 2009; Disetujui: 22 Maret 2010